Perioperative laboratory profiles predict complications after extensive head and neck reconstruction: a proof-of-concept study - Khromov, Tatjana; Breier, Simon; Stefenelli, Ulrich; Schminke, Boris; Schanz, Julie; Fischer, Andreas; Schliephake, Henning; Brockmeyer, Phillipp (Frontiers in Oncology, 2026)
IntroductionSurgical reconstruction of head and neck defects after oncological resection is a complex procedure often associated with unpredictable postoperative complications. Hence, laboratory parameter profiles are of considerable interest as potential perioperative predictors.MethodsThis retrospective study analyzed a comprehensive set of laboratory parameters in 233 patients with oral squamous cell carcinoma (OSCC) who underwent tumor resection and reconstruction.ResultsThe overall complication rate was 30%, with wound dehiscence (12.4%), pulmonary embolism (PE, 11.6%), and surgical revision (10.3%) being the most common complications. Dynamic analysis of perioperative laboratory parameters from one week before to 49 days after surgery revealed that patients who developed complications showed less pronounced decreases in hemoglobin, hematocrit, and erythrocyte levels. These patients also exhibited altered coagulation and electrolyte profiles. Statistical analysis using logistic regression identified hematocrit slope as independent predictor. Meanwhile, random forest modeling highlighted INR and aPTT as key markers. Subgroup analysis showed that PE, the most clinically significant complication, was associated with abnormal potassium, urea, and protein profiles. Whereas a therapy-related increase in aPTT was observed postoperatively, INR alterations were already evident preoperatively. Conversely, local complications such as wound dehiscence, surgical revision, and graft failure were more strongly associated with deteriorating hematological parameters.DiscussionGiven their multifactorial nature, influenced by comorbidities, tumor biology, and perioperative management, these findings highlight the need for longitudinal laboratory monitoring and prospective validation in controlled settings. Integrating dynamic laboratory trends into multimodal prediction models may facilitate earlier risk stratification and improve individualized perioperative management in head and neck reconstructive surgery.